Boiling over: A Descriptive Analysis of Drinking Water Advisories in First Nations Communities in Ontario, Canada - Galway, Lindsay P. (Int J Environ Res Public Health, 2016)
Access to safe and reliable drinking water is commonplace for most Canadians. However, the right to safe and reliable drinking water is denied to many First Nations peoples across the country, highlighting a priority public health and environmental justice issue in Canada. This paper describes trends and characteristics of drinking water advisories, used as a proxy for reliable access to safe drinking water, among First Nations communities in the province of Ontario. Visual and statistical tools were used to summarize the advisory data in general, temporal trends, and characteristics of the drinking water systems in which advisories were issued. Overall, 402 advisories were issued during the study period. The number of advisories increased from 25 in 2004 to 75 in 2013. The average advisory duration was 294 days. Most advisories were reported in summer months and equipment malfunction was the most commonly reported reason for issuing an advisory. Nearly half of all advisories occurred in drinking water systems where additional operator training was needed. These findings underscore that the prevalence of drinking water advisories in First Nations communities is a problem that must be addressed. Concerted and multi-faceted efforts are called for to improve the provision of safe and reliable drinking water First Nations communities.